Cyanidin‐3‐o‐glucoside inhibits UVA‐induced human dermal fibroblast injury by upregulating autophagy. Issue 5 (23rd July 2019) - Wu, Shi; Hu, Yunfeng; Bai, Weibin; Zhao, Jiayi; Huang, Cuiqin; Wen, Caiyan; Deng, Liehua; Lu, Daxiang
Abstract: Background/Purpose: Ultraviolet (UV) A (315‐400 nm) is the UV light that most frequently reaches the Earth's surface and can penetrate the epidermis through to the dermis, causing various issues, including skin aging and skin cancer. The results of our previous studies have shown that the flavonoid monomer cyanidin‐3‐o‐glucoside (C3G) can effectively inhibit primary human dermal fibroblast (HDF) oxidative damage and apoptosis caused by UVA radiation. Many flavonoids can regulate the level of autophagy. However, whether C3G inhibits UVA‐induced oxidative damage to primary HDFs by regulating autophagy levels remains unclear. Methods and Results: In this study, we used different doses (0‐12 J/cm 2 ) of UVA to irradiate cells and showed that the expression levels of autophagy‐related gene 5 (Atg5) and microtubule‐associated protein 1 light chain 3 (LC3)‐II in primary HDFs first increased and then decreased. The expression of Atg5 and LC3‐II was significantly decreased under 12 J/cm 2 (light‐damage model). C3G increased the levels of Atg5 and LC3‐II. Primary HDFs were pretreated with C3G, followed by treatment with the autophagy inhibitor 3‐methyladenine (3‐MA) after 12 J/cm 2 UVA irradiation. The inhibitory effects of C3G on morphological changes, oxidative damage, and apoptosis in primary HDFs induced by UVA were significantly decreased. Conclusion: C3G can inhibit UVA‐induced damage to primary HDFs by inducing autophagy. These results provide a theoretical basis for the application of natural compounds to resist light damage to the skin in the future.